Development of an Environmental Quality Index to Assess Physical Agents Pollution. (September 2020) - Mancini, S; Guida, M; Graziuso, G; Quartieri, J; Guarnaccia, C
Abstract: Among the most common techniques and methodologies for the analysis of the exposure to polluting agents, the definition of environmental indexes represents a very useful tool to easily describe the quality of the environment. Based on experimental measurements, an approach using indicators quantitatively and qualitatively describes the 'health status' of the environments. For this reason, it is considered one of the most clear and efficient tools to support decisions and actions for the competent control authorities. In this paper the development of a general Physical Agents environmental Quality Index (PAQI) describing the potential impact related to the presence of all the different physical pollutants is discussed. The result is represented by a quantity that measures a weighted combination of sub-indices relating to each pollutant and described by means of an appropriate normalized mathematical function. The main idea is to provide an indicator able to describe, in a clear and concise way, the grade of physical pollution of the environment, suggesting in which areas it would be necessary to intervene or not, in order to improve the general environmental conditions.